Parameter Kuda Sandelwood Di Kecamatan Katikutana, Kabupaten Sumba Tengah - Hilarius Langobelen; Frans Umbu Datta; Maxs U E Sanam (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2021)
Horses are one of farm anima that play an important role in human life because it can help alleviate work and as a tool to satisfy human life. The important role of horses is greatly felt by people in Sumba Island. Horses are also be an economic source for most people in Sumba Island. Horses that win the horse race event have a high selling point. The local horse in Sumba Island that used for horse race event is called as the Sandelwood horse. Therefore, the physiological conditions of Sandelwood horse must be maintained. The physiological condition can indicate the health of horse. Basic physiological conditions include the frequency of respiration, heart rate frequency, and body temperature. This study aims to determine the physiological parameters of Sandelwood horses and to determine the relationship between temperature and chest circumference with the physiological condition of Sandelwood horses. This experiment use purposive sampling method. The use of this method is related to the environmental condition and cultural conditions of the Sumbaneses. The results are the enviroment temperature and chest circumference are closely related to the horse activity before measurement and stress levels experienced by the horse at the time of measurement.